2011
DOI: 10.1159/000334456
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Zoledronic Acid on Bone Loss in Postmenopausal Women with Early Breast Cancer Treated with Sequential Tamoxifen and Letrozole: A Prospective, Randomized, Phase II Trial

Abstract: Objective: This study reports the efficacy and safety of zoledronic acid (ZOL) in preventing bone loss in postmenopausal patients receiving an aromatase inhibitor (AI) following tamoxifen. Methods: Postmenopausal patients with stage I–III hormone receptor-positive breast cancer who received tamoxifen for 2.5–3 years were randomized to receive letrozole (2.5 mg/day) with (n = 47) or without (n = 43) ZOL (4 mg i.v. every 6 months) for 2 years. The primary endpoint was percent change from baseline in lumbar spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…The incidence of ONJ in oncology patients treated with i.v. BPs ranges from 0 to 12,222 per 100,000 patient‐years, and the incidence of ONJ in oncology patients treated with Dmab ranges from 0 to 2,316 per 100,000 patient‐years …”
Section: Resultsmentioning
confidence: 99%
“…The incidence of ONJ in oncology patients treated with i.v. BPs ranges from 0 to 12,222 per 100,000 patient‐years, and the incidence of ONJ in oncology patients treated with Dmab ranges from 0 to 2,316 per 100,000 patient‐years …”
Section: Resultsmentioning
confidence: 99%
“…Bisphosphonates have been shown to be effective in numerous studies in preventing cancer treatment-associated bone loss in postmenopausal women with early breast cancer [42][44] mainly due to their effect on the highly activated osteoclasts. Of note, the increase in bone loss is 5-fold higher following treatment with aromatase inhibitors (AIs) than physiological bone loss observed in postmenopausal women with established osteoporosis in the absence of AI therapy, and further induce bone turnover than documented during tamoxifen use [45][49]. A recent study by Cheung indicated that the effect of aromatase inhibitors (exemestane) on bone density may be underestimated and that exemestane increases cortical bone permeability thus predisposing the patient to loss of bone strength and non-vertebral fractures [50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates have been shown to be effective in numerous studies in preventing cancer treatmentassociated bone loss in postmenopausal women with early breast cancer [42][43][44] mainly due to their effect on the highly activated osteoclasts. Of note, the increase in bone loss is 5-fold higher following treatment with aromatase inhibitors (AIs) than physiological bone loss observed in postmenopausal women with established osteoporosis in the absence of AI therapy, and further induce bone turnover than documented during tamoxifen use [45][46][47][48][49]. A recent study by Cheung indicated that the effect of aromatase inhibitors (exemestane) on bone density may be underestimated and that exemestane increases cortical bone permeability thus predisposing the patient to loss of bone strength and non-vertebral fractures [50][51].…”
Section: Discussionmentioning
confidence: 99%